MOLECULAR SEQUENCE-BASED POLYMORPHISMS IN THE INSULIN LIKE GROWTH FACTOR (IGF-I) OF NILE TILAPIA (Oreochromis niloticus) FROM DIFFERENT WATER BODIES - OGUNTADE, O.R; SOKENU , B.A (Nigerian Journal of Fisheries, 2021)
In recent years, salinity levels in the Senegal River Delta have been altered by sea-level changes with significant transgressions and regressions which has had a severe impact on freshwater fish farm productions throughout the region. The high salt in a tilapia fish farm location is considered potentially stressful to fish and, therefore, predisposing to pathologies and slow growth. This study was aimed at identifying the variability and assessing the novel nucleotide and amino acid polymorphism present in the growth gene of Oreochromis niloticus from the two West African sub-regions (Nigeria and Senegal). All individual samples from Epe river, Nigeria (ONN), and Senegal river basin by Diama (ONS) were screened for genetic variation by a gene-specific PCR reaction with the primers (IGF-I forward-5’-CTTGGACGAGTAGGAGGCAAATG-3’and IGF-I reverse- 3’- AAATACAAGCAAGCGATAAGAA-5’) of 447 bp (IGF-I, GenBank accession AF033797). Nucleotide and amino acid (AA) sequences obtained were edited and aligned and a phylogram was created using Clustal O (version1.2.4) multiple sequence alignment software. High polymorphisms were detected for both the nucleotides and amino acids on selected strains of the tilapia and the phylogenetic tree generated revealed lower similarities between ONN and ONS and higher similarities among ONN1 and ONN2 and ONS1 and ONS2. This study provides additional information regarding variation in insulin growth factor I of O. niloticus that could promote association study for production traits. Keywords: , , , , and